Haemoglobin drop in patients with myocardial infarction and without previous anaemia is associated with an increased incidence of heart failure and cardiogenic shock. (3rd May 2023) - Paralta De Figueiredo, M; Carias, M; Picarra, B; Rocha De Almeida, A; Claudio, F; Rocha, R; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: It is established that the presence of anaemia is associated with a higher number of complications in patients with myocardial infarction (MI). However, even in patients without history of anaemia, haemoglobin (Hb) drop is often observed. The impact of this decrease in the incidence of heart failure (HF), cardiogenic shock (CS) and reinfarction is still unclear. Purpose: This retrospective observational study aims to document if a drop of Hb greater than 2g/dL in patients with MI and without previous anaemia relates to higher rates of HF, CS and reinfarction. Methods: We selected a population of 4287 patients admitted with MI with initial Hb between 12 and 15g/dL and without major bleeding at admission (D). We then divided them in two groups: those with a drop of Hb ≥ 2g/dL (D1) and those with an inferior drop (D2) Patient's age, gender, personal history, clinical and electrocardiographic presentation of MI, in-hospital therapy, coronary angiography and left ventricular function were recorded. The incidence of reinfarction, HF and CS was documented. In-hospital mortality was also compared. Multivariate analysis was performed to evaluate whether a drop in Hb was an independent predictor of any of these events. Results: D1 consisted of 17, 9% of the population (N=863). D1 presented with lower Hb values when compared to D2 (11 ± 1.1 vs 12.9 ± 1.0 g / dL, p < 0.001). These patients were older (70 ± 12 vs 65 ± 13 years, p<0.001), more frequently of the female sex (41, 6 vs 27, 2%, p<0.001), had a higher prevalence of hypertension (73, 3% vs 65, 7% p<0.001), diabetes mellitus (36, 9 vs 26, 9%, p<0, 001), history of HF (5, 9 vs 4, 0%, p=0, 013) and chronic renal failure (5, 8% vs 3, 8%, p=0, 003). At the time of admission, D1 underwent more therapy with unfractionated heparin (34, 6% vs 26, 2%, p<0.001), enoxaparin (66, 7% vs 51, 7%, p<0.001) and less therapy with fondaparinux (12, 7% vs 18, 3%, p<0.001). The coronary angiography rate was similar between the groups, but D1 had more frequently the need for repeat angiography (10, 7% vs 6, 6%, p<0, 001), more coronary angiographies by femoral access (40, 2% vs 20, 2%, p<0.001) and more angioplasties (71, 9% vs 68, 4%, p=0, 04). D1 presented more frequently with HF (24, 8% vs 11, 1%, p<0, 001), cardiogenic shock (10, 5% vs 1, 7%, p<0, 001), reinfarction (2, 1% vs 1, 1%, p=0, 011) and had significantly higher in-hospital mortality (5, 0% vs 2, 0%, p<0, 001). A drop of Hb≥2g/dL was an independent predictor of reinfarction, HF and CS, but not IHM. Conclusions: In patients with MI and without previous anaemia nor major bleeding at admission, haemoglobin drop is a predictor of heart failure, cardiogenic shock and reinfarction, but not of in-hospital mortality.